The TB and HIV/AIDS Epidemics in the Russian Federation - Vinokur, Anatoly (Washington, DC: World Bank, 2013)
The Russian Federation has been confronting a major epidemiological crisis, which will have considerable human and economic costs if it is not swiftly addressed. Between 1999 and 2000, the country experienced the world's biggest increase in new cases of HIV/AIDS infection. The TB epidemic is at risk of becoming uncontrollable if the country experiences a moderate epidemic of HIV/AIDS. This report represents the analysis and recommendations of a group of experts from the World Health Organization and the World Bank, and focuses on the current epidemiological situation in the Russian Federation and the existing institutional arrangements available to tackle both epidemics. It encompasses projections for the TB epidemic, the interaction with the HIV/AIDS epidemic, and the impact of a spiraling duel epidemic. The report has four sections. The first briefly describes socioeconomic conditions. The second section discusses the impact on the population of the epidemic, incidence and prevalence in the general and prison populations, diagnosis and treatment processes, and current TB management and control structures. The third section profiles the HIV/AIDS epidemic and its impact, and the role of STIs in fostering the disease. Finally, the fourth section describes a mathematical model of health improvements possible under various TB control strategies with implications for HIV/aids as well.